CHILDHOOD OBESITY AS A PREDICTOR OF TYPE 2 DIABETES MELLITUS IN ADULTS : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The United States of America and other countries all over the world are not the only ones experiencing a growing epidemic of childhood obesity as a major threat to public health. This is a problem that affects countries in all parts of the world. At the moment, one child in the United States out of every three is either overweight or obese. This problem is especially prevalent among young people. Obesity treatments need to be community-based and environment-focused in order to put an end to the epidemic of obesity. As the prevalence of pediatric obesity continues to climb, comorbidities that were once regarded of as "adult" illnesses, such as type 2 diabetes mellitus, hypertension, nonalcoholic fatty liver disease, obstructive sleep apnea, and dyslipidemia, are becoming increasingly common in children. Even a slight gain in weight before puberty is associated with an increased risk of type 2 diabetes and cardiovascular disease later in life; hence, immediate action is required. The presence of insulin in the bloodstream despite a decreased tissue sensitivity to insulin is characteristic of type 2 diabetes. There is a strong correlation between being overweight or obese and developing type 2 diabetes. As a result, the hypothesis that overeating is the root cause of Type 2 Diabetes. Due to muscle and islet -cell insulin resistance, which promotes greater glucagon production, obesity raises the chance of developing type 2 diabetes mellitus in persons who are already genetically susceptible to developing the condition. On the other hand, obesity is not the primary risk factor for developing type 2 diabetes.